Early diagnostic value of high‐sensitivity cardiac troponin T for cancer treatment‐related cardiac dysfunction: a meta‐analysis - Xinfang Lv; ChenLiang Pan; Huan Guo; Juan Chang; Xiang Gao; Xue Wu; Xiaodong Zhi; Chunzhen Ren; Qilin Chen; Hugang Jiang; Xinke Zhao; Kai Liu; et al. (ESC Heart Failure, 2023)
Abstract Early diagnosis of cancer treatment‐related cardiac dysfunction (CTRCD) is important as cancer therapy increases the risk of cardiac dysfunction. High‐sensitivity cardiac troponin T (hs‐cTnT) is a highly specific marker of myocardial injury. However, its diagnostic value for CTRCD has not been systematically evaluated. This meta‐analysis aimed to evaluate whether hs‐cTnT could be used as an early diagnostic biomarker for CTRCD. We systematically surveyed PubMed, Embase, Cochrane Library, and Web of Science databases for studies of hs‐cTnT for the diagnosis of CTRCD before 1 April 2022. Patients of all ages and all cancer types who underwent echocardiographic left ventricular ejection fraction assessment and blood hs‐cTnT and received anticancer therapy (including chemotherapy, radiotherapy, targeted therapy, immune checkpoint inhibitors, and other treatments) were included in this study, resulting in a total of eight studies with 1294 patients. The occurrence of CTRCD was associated with elevated hs‐cTnT [sensitivity: 0.78, 95% confidence interval (CI): 0.64–0.88; specificity: 0.75, 95% CI: 0.59–0.86; area under the curve (AUC): 0.83, 95% CI: 0.80–0.86]. We further performed subgroup analysis and found that the AUC of hs‐cTnT elevation for the diagnosis of CTRCD increased from 0.83 to 0.90 (95% CI: 0.87–0.92) at 3–6 months, suggesting a higher early diagnostic value of hs‐cTnT compared with echocardiography for CTRCD. In terms of clinical applicability, the Fagan plot showed pre‐test and post‐test probabilities of 51% and 9%, respectively, indicating that hs‐cTnT testing can improve the accuracy of clinical diagnosis of CTRCD. However, it was not possible to determine the optimal cut‐off value for early diagnosis of CTRCD with hs‐cTnT. The Deeks funnel plot was largely symmetrical (P = 0.74); hence, publication bias was not observed. Hs‐cTnT allowed early CTRCD diagnosis at 3–6 months. However, further high‐quality research is needed to determine the optimal cut‐off value for early CTRCD diagnosis with this biomarker.